Persons with Disabilities and Legal Aid as A Form of Protection - K Kuswardani; Kiki Samudera (Proceeding International Conference Restructuring and Transforming Law, 2023)
Discriminatory treatment of people with disabilities occurs in various fields, one effort to eliminate this treatment is to involve the legal profession by providing legal services in the form of assistance, help or support. The legal services provided should be in accordance with the provisions of the law on persons with disabilities. This research uses empirical legal research sourced from observations, literature studies and interviews. The data used in this research is primary and secondary data which shows that there are various problems in the law enforcement process, especially those related to disabilities in dealing with the law, so there needs to be commitment from both the duty bearer, the legal profession and the community.